OP8 Are clinically obese children at increased risk of hospital admission? a longitudinal analysis using linked electronic health records in wales and scotland. (September 2018) - Griffiths, LJ; Cortina-Borja, M; Bandyopadhyay, A; Tingay, K; De Stavola, BL; Bedford, H; Akbari, A; Lyons, R; Dezateux, C
Abstract : Background: Few studies have examined the extent and nature of health service utilisation by obese and overweight children. We estimated the rate of hospital admission from five to 13.9 years of age in children who were clinically overweight or obese by age five years compared with their healthy weight peers, using linked electronic health records from a nationally representative prospective cohort of children in Wales and Scotland. Methods: Data were available for 3306 singleton children participating in the Millennium Cohort Study (MCS), who were living in Wales (n=1840) or Scotland (n=1466), and whose parents consented to linkage to their health records up until their 14th birthday. Height and weight were measured at home interview at age five years and weight status was categorised according to the UK1990 clinical reference standards. Overall, 3269 (1678 boys) of these 3306 (98.9%) children were linked to the Welsh Demographic Service (n=1838) or their Scottish Community Health Index number (n=1431) via probabilistic and deterministic record matching. In turn, they were matched to Welsh and Scottish hospital admission records from the Patient Episode Database for Wales, and Scottish Morbidity Records, respectively. Using information on admissions from five to 14 years, we fitted negative binomial models adjusted by potential confounders in order to compare rates of inpatient admissions from any cause, for diseases of the digestive or respiratory system, or for injuries by weight status at age five. Results: At age 5, 11.6% and 6.8% of children were overweight or obese respectively, and 37% had at least one subsequent hospital admission by their 14th birthday. Compared to children of a healthy weight, there was no increase in the rate of all-cause hospital admissions among overweight or obese children (confounder-adjusted rate ratio (RR), 95% confidence interval (CI): 0.9 (0.7, 1.1) and 1.2 (0.9, 1.5), respectively), or with diseases of the digestive or respiratory system or with injuries. Conclusion: This is to our knowledge the first study to link childhood weight status to hospital admissions in a nationally representative cohort. We found that clinical obesity at primary school entry is not associated with a higher rate of subsequent hospital admissions up to age 14 years in children born in 2000/2001. Future analyses will examine primary care consultations and accident and emergency attendances. Longer-term follow up is also needed to determine whether rates increase with age.